2002
DOI: 10.1029/2001gl013842
|View full text |Cite
|
Sign up to set email alerts
|

Driven Alfven waves and electron acceleration: A FAST case study

Abstract: [1] Observations of electric and magnetic field oscillations and accelerated electron distributions within an inverted-V region suggest the propagation of an Alfven wave from the outer magnetosphere into the auroral acceleration region. This hypothesis is tested for a case study event by simulating the propagation of an Alfven wave driven by an oscillating potential in the outer magnetosphere. At the spacecraft altitude the waveform and the associated electron distributions and spectra formed due to accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 18 publications
10
148
1
Order By: Relevance
“…However, the FAST spacecraft [e.g., Chaston et al, 2000Chaston et al, , 2002aChaston et al, , 2003Chaston et al, , 2006Chaston et al, , 2007 has observed these broadband distributions in conjunction with Alfvénic fluctuations, suggesting that these electrons are accelerated by parallel electric fields in kinetic Alfvén waves. This conclusion was supported by models for the Alfvén wave acceleration of these electrons [e.g., Kletzing, 1994;Thompson and Lysak, 1996;Chaston et al, 1999Chaston et al, , 2000Chaston et al, , 2002aChaston et al, , 2002bKletzing and Hu, 2001;Lysak and Song, 2003a, 2003b, which gave results consistent with observation. Thus, such events have been termed the "Alfvénic aurora.…”
Section: Introductionmentioning
confidence: 99%
“…However, the FAST spacecraft [e.g., Chaston et al, 2000Chaston et al, , 2002aChaston et al, , 2003Chaston et al, , 2006Chaston et al, , 2007 has observed these broadband distributions in conjunction with Alfvénic fluctuations, suggesting that these electrons are accelerated by parallel electric fields in kinetic Alfvén waves. This conclusion was supported by models for the Alfvén wave acceleration of these electrons [e.g., Kletzing, 1994;Thompson and Lysak, 1996;Chaston et al, 1999Chaston et al, , 2000Chaston et al, , 2002aChaston et al, , 2002bKletzing and Hu, 2001;Lysak and Song, 2003a, 2003b, which gave results consistent with observation. Thus, such events have been termed the "Alfvénic aurora.…”
Section: Introductionmentioning
confidence: 99%
“…Lysak (1993) included electron inertia and a more realistic V A profile based on a dipole magnetic field to show that effects from the resonator persisted when parallel electric fields were present. This model was used to investigate electron acceleration through test particle models (Thompson and Lysak, 1996;Chaston et al, 2000Chaston et al, , 2002a, indicating that field aligned beams of electrons observed from the FAST satellite were consistent with acceleration due to parallel electric fields in the resonator.…”
Section: Discussionmentioning
confidence: 99%
“…Broadband acceleration in upward, downward, or no FAC regions can be attributed to small-scale dispersive Alfvén waves that create time-varying field-aligned electric field that disperses electron energy [e.g., Chaston et al, 2002;Watt and Rankin, 2009;Wing et al, 2013]. On the other hand, monoenergetic electrons are usually attributed to quasi-static potential drops, which are typically associated with upward FAC regions and global magnetic field configuration or low-frequency waves [Damiano and Johnson, 2012].…”
Section: 1002/2015gl064229mentioning
confidence: 99%